GABA release by basket cells onto Purkinje cells, in rat cerebellar slices, is directly controlled by presynaptic purinergic receptors, modulating Ca2+ influx - Donato, Roberta (2008)
In many brain regions, Ca2+ influx through presynaptic P2X receptors influences GABA release from interneurones. In patch-clamp recordings of Purkinje cells (PCs) in rat cerebellar slices, broad spectrum P2 receptor antagonists, PPADS (30 [mu]M) or suramin (12 [mu]M), result in a decreased amplitude and increased failure rate of minimal evoked GABAergic synaptic currents from basket cells. The effect is mimicked by desensitizing P2X1/3-containing receptors with [alpha],[beta]-methylene ATP. This suggests presynaptic facilitation of GABA release via P2XR-mediated Ca2+ influx activated by endogenously released ATP. In contrast, activation of P2Y4 receptors (using UTP, 30 [mu]M, but not P2Y1 or P2Y6 receptor ligands) results in inhibition of GABA release. Immunological studies reveal the presence of most known P2Rs in >=20% of GABAergic terminals in the cerebellum. P2X3 receptors and P2Y4 receptors occur in approximately 60% and 50% of GABAergic synaptosomes respectively and are localized presynaptically. Previous studies report that PC output is also influenced by postsynaptic purinergic receptors located on both PCs and interneurones.